Sleep-Disordered Breathing Is Associated With Recurrent Ischemic Stroke. Issue 3 (March 2019) - Brown, Devin L.; Shafie-Khorassani, Fatema; Kim, Sehee; Chervin, Ronald D.; Case, Erin; Morgenstern, Lewis B.; Yadollahi, Azadeh; Tower, Susan; Lisabeth, Lynda D.
Abstract : Background and Purpose—: Limited data are available about the relationship between sleep-disordered breathing (SDB) and recurrent stroke and mortality, especially from population-based studies, large samples, or ethnically diverse populations. Methods—: In the BASIC project (Brain Attack Surveillance in Corpus Christ), we identified patients with ischemic stroke (2010–2015). Subjects were offered screening for SDB with the ApneaLink Plus device, from which a respiratory event index (REI) score ≥10 defined SDB. Demographics and baseline characteristics were determined from chart review and interview. Recurrent ischemic stroke was identified through active and passive surveillance. Cause-specific proportional hazards models were used to assess the association between REI (modeled linearly) and ischemic stroke recurrence (as the event of interest), and all-cause poststroke mortality, adjusted for multiple potential confounders. Results—: Among 842 subjects, the median age was 65 (interquartile range, 57–76), 47% were female, and 58% were Mexican American. The median REI score was 14 (interquartile range, 6–26); 63% had SDB. SDB was associated with male sex, Mexican American ethnicity, being insured, nonsmoking status, diabetes mellitus, hypertension, lower educational attainment, and higher body mass index. Among Mexican American and non-Hispanic whites, 85 (11%) ischemic recurrent strokes and 104 (13%) deaths occurred, with a median follow-up time of 591 days. In fully adjusted models, REI was associated with recurrent ischemic stroke (hazard ratio, 1.02 [hazard ratio for one-unit higher REI score, 95% CI, 1.01–1.03]), but not with mortality alone (hazard ratio, 1.00 [95% CI, 0.99–1.02]). Conclusions—: Results from this large population-based study show that SDB is associated with recurrent ischemic stroke, but not mortality. SDB may therefore represent an important modifiable risk factor for poor stroke outcomes.